1990
DOI: 10.3109/07420529009059156
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values for Orcadian Rhythms of 98 Variables in Clinically Healthy Men in the Fifth Decade of Life

Abstract: Nine clinically healthy men, 41-47 yr of age, served as subjects in a 24-hr study conducted at the Edward Hines Jr Veterans Administration Hospital in the Chicago area in May 1988. Physiologic measurements, and blood and urine samples were collected at 3-hr intervals over a single 24-hr period beginning at 1900. The number of variables measured or calculated (total = 98) included: 6 vital signs (oral temperature, pulse, blood- and intraocular pressures); 16 in whole blood (counts and differentials); 50 in seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 6 publications
3
19
0
Order By: Relevance
“…In this context, significant correlations between resting core temperature and LDH and between WBC and CK and LDH were registered. These findings confirmed that the presence of leucocytosis at a specific TOD could be due to the high concentrations of catecholamines (23) and to the general increase in muscle damage (34). The present study showed higher antioxidant activity in the evening and no diurnal variation for MDA.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In this context, significant correlations between resting core temperature and LDH and between WBC and CK and LDH were registered. These findings confirmed that the presence of leucocytosis at a specific TOD could be due to the high concentrations of catecholamines (23) and to the general increase in muscle damage (34). The present study showed higher antioxidant activity in the evening and no diurnal variation for MDA.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, the authors suggest the existence of further underlying mechanisms [i.e., such as catecholamine Kanabrocki et al (23)] which can be in the origin of muscle damage response to high-intensity weightlifting exercises. Concerning the CRP, our results showed the absence of diurnal variations at resting state and immediately and 48 h after the training sessions.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that physiology being quantified by these tests may be more dynamic than is appreciated in the clinical interpretation of their results. Although a wealth of clinical laboratory testing data exists (10)(11)(12), the circadian or physiological periodicity of many common laboratory blood tests may need additional evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that biochemical markers of cellular damage (Kanabrocki et al 1990;Rivera-Coll et al 1993;Gutenbrunner 2000), as well as WBC and their subpopulations (Haus et al 1983), are time-of-day (TOD)-dependent with acrophases generally observed in the evening. The acrophases for the quantities studied coincide with times near those of the oral temperature acrophase (Rivera-Coll et al 1993).…”
Section: Introductionmentioning
confidence: 99%